Detection of Dientamoeba fragilis in patients with HIV/AIDS by using a simplified iron hematoxylin technique - Garcia,Juliana Alves (2012)
INTRODUCTION: Studies strongly indicate Dientamoeba fragilis as one of the causes of diarrhea in human immunodeficiency virus (HIV) patients. METHODS: The objective of the present study was to evaluate the prevalence of D. fragilis associated with the causes of diarrhea in 82 HIV/ AIDS patients hospitalized at the Instituto de Infectologia Emílio Ribas from September 2006 to November 2008. RESULTS: In total, 105 samples were collected from 82 patients. Unprotected sex was the most frequent cause of HIV infection (46.3%), followed by the use of injectable or non-injectable drugs (14.6%). Patients presented with viral loads of 49-750,000 copies/ mL (average: 73,849 ± 124,850 copies/mL) and CD4 counts ranging of 2-1,306 cells/mm³ (average: 159 ± 250 cells/mm³). On an average, the odds of obtaining a positive result by using the other techniques (Hoffman, Pons and Janer or Lutz; Ritchie) were 2.7 times higher than the chance of obtaining a positive result by using the simplified iron hematoxylin method. Significant differences were found between the methods (p = 0.003). CONCLUSIONS: The other techniques can detect a significantly greater amount of parasites than the simplified iron hematoxylin method, especially with respect to Isospora belli, Cryptosporidium sp., Schistosoma mansoni, and Strongyloides stercoralis, which were not detected using hematoxylin. Endolimax nana and D. fragilis were detected more frequently on using hematoxylin, and the only parasite not found by the other methods was D. fragilis.